Computation of drift forces for dynamic positioning within the very early design stage of offshore wind farm installation vessels - Augener, Philip Herbert; Krüger, Stefan (Volume 1A: Offshore Technology, 2014)
The German government has decided upon the changeover from fossil and nuclear based electrical power generation to renewable energies. Following from this offshore wind farms are erected in the exclusive economic zones of Germany. For the transportation and installation as well as the maintenance of the wind turbine generators very specialized vessels are needed. The capability of dynamic positioning even in very harsh weather conditions is one of the major design tasks for these vessels. For this reason it is important to know the external loads on the ships during station keeping already in the very early design stage. This paper focuses on the computation of wave drift forces in regular and irregular waves as well as in natural seaway. For validation the results of the introduced calculation procedure are compared to measured drift force data from sea-keeping tests of an Offshore Wind Farm Transport and Installation Vessel.